Pseudomonas aeruginosa and Pseudomonas spp. isolated from fresh Minas cheeses in Rio de Janeiro - Newton Okuno; Isabela Freire; Cristiane Silva; Victor Marin (Revista de Ciência Veterinária e Saúde Pública, 2021)
Pseudomonas aeruginosa is an opportunistic pathogen among the most prevalent nosocomial microorganisms and is particularly relevant to the health of infants, children, and immunocompromised persons. P. aeruginosa is linked to gastroenteritis and causes the Shanghai fever with necrotizing enteritis and sepsis infants and children, and, albeit rare, necrotizing enteritis in adults. Cheeses with high moisture content are issues of concern to the health of that population as the already present pathogens can easily grow. In this work, P. aeruginosa and Pseudomonas spp. strains were found, respectively, in 04 (12.1%) and 19 (57.6%) of 33 samples of fresh Minas cheese, a traditional Brazilian cheese, acquired from May 2015 to January 2016 in Rio de Janeiro city. Antimicrobial susceptibility testing of 03 P. aeruginosa strains was performed with ticarcillin, ticarcillin-clavulanic acid, ceftazidime, cefepime, aztreonam, imipenem, meropenem, gentamicin, ciprofloxacin, and colistin. Although no resistance to these antimicrobials was found, good manufacturing and hygienic practices in dairy plants are paramount to ensure food safety and quality. Furthermore, surveillance of antibiotic resistance and opportunistic pathogens with resistance genes in the dairy chain is useful to control the spread of antibiotic resistance.